A preparation method of oxygen-insulated luminous plastic

By using homemade filler aerogel hollow microspheres and modified aerogel microcolumns in foam plastics, combining graphene and propargyl carbamate structures to form a conductive network, the resistance of foam plastics in electronic product packaging is solved. Static electrostatic, mildew protection and shock absorption problems have achieved better compatibility and performance improvements.

CN117965018BActive Publication Date: 2024-12-24GUANGDONG JINGJING ENVIRONMENTAL PROTECTION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311737259.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-06
Publication Date
2024-12-24
Estimated Expiration
2043-04-06

AI Technical Summary

Technical Problem

During transportation, existing foam plastics have problems such as poor anti-static effect, poor compatibility and insufficient anti-mold performance. Especially in packaging materials of electronic products, it is difficult to achieve shock absorption, anti-mold and anti-static functions at the same time.

Method used

The homemade filler is combined with aerogel hollow microspheres and modified aerogel microcolumns to form a conductive network through graphene aerogel microcolumns and propargyl carbamate structures, and combines 3-aminopropyltrimethoxysilane. Grafting reaction to prepare oxygen-insulated luminous plastic with luminous effect.

Benefits of technology

The shock absorption, mildew and anti-static effects of plastics are achieved, while improving compatibility with resin matrix, enhancing conformational distribution, and improving the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention discloses a method for preparing oxygen-barrier luminescent plastic, relating to the field of plastics technology. The invention utilizes graphene aerogel micropillars as the elastic support of the plastic, loading rare earth aluminates inside the aerogel. Then, a polyaniline conductive network is formed on the surface of the graphene aerogel micropillars using 3-aminopropyltrimethoxysilane and (E)-3-(3-nitrophenyl)acryloyl chloride, improving antistatic and shock-absorbing effects. Next, an antifungal monomer compound is prepared using 5-(2-chloroethanelamino)-2-hydroxybenzoic acid, propargyl chloroformate, and 1-(5-bromo-2-hydroxyphenyl)-3-(diethylamino)-2-propen-1-one. Using polystyrene hollow spheres as a template, it is cross-linked with formaldehyde to prepare aerogel hollow microspheres. These microspheres are then deposited onto the modified aerogel micropillars using ultraviolet light to obtain a self-made filler. This filler is then co-foamed with polyurethane to form a foam plastic, achieving shock absorption, antifungal, and antistatic effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastics, in particular to a method for preparing oxygen-insulated luminous plastics. Background Art

[0002] During transportation, items are usually cushioned and protected by foam plastics, such as polystyrene, polyethylene, polyurethane and other foam plastics. For electronic products that are susceptible to static electricity, such as integrated circuits and communication equipment, packaging materials need to have antistatic functions. The antistatic function of the material is usually added with conductive filler carbon black. Although it can achieve long-term stable antistatic performance, it affects the appearance and has poor compatibility, resulting in unsatisfactory antistatic effect.

[0003] Since foam plastic materials contain nutrients necessary for bacteria, mold, etc., microorganisms such as bacteria and mold will multiply in large numbers under suitable temperature and humidity conditions, and mold secretions will cause biodegradation of foam plastics. As people's living standards improve, more and more fields have put forward higher requirements on the hygienic properties of materials, so there are corresponding requirements for the antibacterial properties of foam plastics. Summary of the invention

[0004] The purpose of the present invention is to provide an oxygen-insulated luminous plastic and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: an oxygen-insulating luminous plastic, which mainly includes a self-made filler, a flame retardant, a polyhydroxy compound, and a polyisocyanate compound.

[0006] Furthermore, the self-made filler is prepared by depositing aerogel hollow microspheres on modified aerogel microcolumns under ultraviolet light.

[0007] Furthermore, the aerogel hollow microspheres are prepared by preparing an anti-mildew monomer compound from 5-(2-chloroethaneamido)-2-hydroxy-benzoic acid, propargyl chloroformate, and 1-(5-bromo-2-hydroxyphenyl)-3-(diethylamino)-2-propene-1-one, and then cross-linking with formaldehyde using polystyrene hollow spheres as a template.

[0008] Furthermore, the modified aerogel microcolumn is prepared by the following method: injecting a graphene solution into a columnar in-situ forming mold, using this as a template to prepare a graphene aerogel microcolumn, then soaking and adsorbing a luminous powder precursor solution, sol-gel, and calcining to obtain a luminous aerogel microcolumn; then using 3-aminopropyltrimethoxysilane and (E)-3-(3-nitrophenyl) acryloyl chloride for modification to obtain a modified aerogel microcolumn.

[0009] Furthermore, the flame retardant is prepared by mixing diethyl phosphate, dimethyl methylphosphonate, and aluminum phenylphosphinate; the polyhydroxy compound is one or a mixture of polyester polyols with a relative molecular weight of 1000-4000, polyether polyols with a relative molecular weight of 2000-6500, or sorbitol; and the polyisocyanate compound is one or a mixture of hexamethylene diisocyanate and diphenylmethane diisocyanate.

[0010] Furthermore, a method for preparing oxygen-insulated luminous plastic comprises the following preparation steps:

[0011] (1) A propargyl carbamate compound, potassium iodide, tetrahydrofuran, and 1-(5-bromo-2-hydroxyphenyl)-3-(diethylamino)-2-propene-1-one were mixed in a mass ratio of 1:0.1:18:2 to 1:0.2:18:3, reacted at 80 rpm and 82°C for 46 to 50 hours, filtered, and the filter cake was washed twice with methanol and distilled water in sequence, and dried at 50°C and a vacuum degree of -0.08 MPa for 24 hours to obtain an anti-mildew monomer compound;

[0012] (2) Mix the polystyrene hollow spheres and the mildew-proof monomer compound solution in a mass ratio of 1:2 to 1:4, place at 25°C for 40 to 48 hours, add dibutyl phthalate with an equal volume of the mildew-proof monomer compound solution, heat to 35°C, stir at 100 to 120 rpm for 24 hours, filter, take the solid, immerse it in acetone 3 to 4 times the mass of the solid, soak it for 48 hours to obtain wet gel microspheres, place it in an autoclave, cool it to 4 to 6°C, fill it with liquid carbon dioxide to 2 to 4 times the height of the wet gel microspheres, maintain it at 31°C and 7.3 MPa for 30 to 40 minutes, then increase the pressure to 8 to 10 MPa, increase the temperature to 45 to 50°C, maintain it for 2 to 4 hours, and then release the pressure to normal pressure to obtain aerogel hollow microspheres;

[0013] (3) The aerogel microcolumn is placed in a luminescent powder precursor solution with a mass of 0.5 to 1.2 times that of the aerogel microcolumn. The mass ratio of strontium chloride, europium nitrate, crystalline aluminum chloride, deionized water, and citric acid in the luminescent powder precursor solution is 1.02:0.07:1.97:40:2.52. After ultrasonic treatment at 90°C and 500W for 1 to 2 hours, the aerogel microcolumn is taken out and placed in a 110°C oven. After drying for 10 to 20 hours, the aerogel microcolumn is placed in a tubular heat treatment furnace and heated to 700°C at a rate of 10°C / min. After keeping the temperature for 2 to 3 hours, the aerogel microcolumn is cooled to room temperature. In a reducing atmosphere, the temperature is raised to 900 to 1200°C at the same rate. The aerogel microcolumn is sintered for 4 hours. The volume ratio of nitrogen and hydrogen in the reducing atmosphere is 95:5. The aerogel microcolumn is cooled to room temperature to obtain a luminescent aerogel microcolumn.

[0014] (4) Mix the luminous aerogel microcolumn and deionized water in a mass ratio of 5:1200, stir evenly, add 3-aminopropyltrimethoxysilane solution with a mass of 6 to 13 times the mass of the luminous aerogel microcolumn, the mass ratio of 3-aminopropyltrimethoxysilane solution to anhydrous ethanol in the 3-aminopropyltrimethoxysilane solution is 1:19 to 1:32, ultrasonicate at 400 to 500 W for 30 min, stir at 100 to 120 rpm for 10 min, add hydrochloric acid until the solution pH is 4 to 5, react in a water bath at 50 ° C for 2 to 3 h, heat to 70 ° C, continue to react for 2 to 3 h, centrifuge at 18000 rpm for 3 to 5 min, and filter to obtain the pretreated aerogel microcolumn;

[0015] (5) The pretreated aerogel microcolumn, tetrahydrofuran, and N,N-dimethylformamide were mixed in a mass ratio of 1:6:5.1. At 0°C, 4-5 times the mass of the pretreated aerogel microcolumn (E)-3-(3-nitrophenyl) acryloyl chloride solution was added dropwise. The mass ratio of (E)-3-(3-nitrophenyl) acryloyl chloride to tetrahydrofuran in the (E)-3-(3-nitrophenyl) acryloyl chloride solution was 1:3.5. After stirring at 60-80 rpm for 48 h, 80-85 times the mass of the pretreated aerogel microcolumn was added with distilled water. After stirring at 100-200 rpm for 20-30 min, the mixture was filtered, washed with deionized water for 4 times, and dried at 40°C and vacuum degree of -0.07 MPa for 12 h to obtain the amidated aerogel microcolumn.

[0016] (6) Tetrahydrofuran, amidated aerogel microcolumns, deionized water, iron powder, and 7.5% hydrochloric acid were mixed in a mass ratio of 10:1:3:1.6:0.5-12:1:4:1.9:0.6, and reacted for 7-8 hours. Then, ethyl acetate (4 times the mass of the amidated aerogel microcolumns) and sodium hydroxide (0.06 times the mass of the amidated aerogel microcolumns) were added. After reacting at 50°C for 30-40 minutes, the mixture was filtered and washed with ethyl acetate and saturated sodium chloride for 5 times to obtain intermediate A. The mixture with a mass fraction of 4. 4% hydrochloric acid, intermediate A, and aniline are mixed in a mass ratio of 20:1:1.0-30:1:1.5, stirred evenly, and then an ammonium persulfate solution of 19-20 times the mass of the intermediate A is added, and the mass ratio of ammonium persulfate to 4.4% hydrochloric acid in the ammonium persulfate solution is 1:15. After reacting for 23-25 ​​hours, the mixture is filtered, washed with 4.4% hydrochloric acid, ethanol, and distilled water for 6 times in sequence, and dried at 50°C and a vacuum degree of -0.09 MPa for 24 hours to obtain a modified aerogel microcolumn;

[0017] (7) Polyvinyl pyrrolidone, methanol, modified aerogel microcolumns, aerogel hollow microspheres, and azobisisobutyronitrile were mixed in a mass ratio of 3.5:68:8.4:4.1:1.2-5.7:83:17.0:8.0:1.2, and ultrasonicated for 15 min at 400-500 W, and then evacuated to 0.1-0.5 Pa with an intensity of 0.7 mW / cm 2 , after irradiating with ultraviolet light of wavelength 254nm for 24-26h, centrifuging at 15000rpm for 5-8min, filtering, washing with deionized water and anhydrous ethanol for 4 times in sequence, and drying at 0℃ and vacuum degree of -0.09MPa for 24h to obtain the self-made filler;

[0018] (8) Mix polyhydroxy compounds, flame retardants, homemade fillers, foam stabilizers, blowing agents, and catalysts in a mass ratio of 100:10:10:0.1:1:0.01~150:20:30:5.0:5:2.0. The mass ratio of diethyl phosphate, dimethyl methylphosphonate, and phenyl phosphinate aluminum in the flame retardant is 1:1.0:1.0~1:1.3:1.5. After stirring evenly, add a polyisocyanate compound of 0.4~0.5 times the mass of the polyhydroxy compounds, react at 30~40℃ and 100~200rpm for 2~3h, inject into a mold at 50~60℃, let stand for 10~20min, put into an oven at 70~90℃, mature for 1~2h, cool and demold, and obtain an oxygen-insulated luminous plastic.

[0019] Furthermore, the preparation method of the propargyl carbamate compound in step (1) is: 5-(2-chloroethaneamido)-2-hydroxy-benzoic acid and pyridine are mixed in a mass ratio of 1:7, cooled to 0°C, 0.1-0.2 times the mass of pyridine propargyl chloroformate is added, reacted at 0-4°C for 2h, ice water is added until solid is precipitated, and filtered to obtain the propargyl carbamate compound.

[0020] Furthermore, in the step (2), the mass ratio of the anti-mildew monomer compound, formaldehyde, sodium hydroxide and ethanol in the anti-mildew monomer compound solution is 1:0.5:0.007:2.7 to 1:0.8:0.007:3.5.

[0021] Furthermore, the preparation method of the aerogel microcolumn in step (3) is as follows: injecting a graphene solution into a cylindrical in-situ molding mold with a diameter of 850 μm to 2 / 3 of the height of the cylindrical in-situ molding mold, wherein the mass ratio of graphene oxide, deionized water, and vitamin C in the graphene solution is 0.4:100:0.8, placing the solution in an oven at 80°C, reacting for 60 minutes, cooling to room temperature, freezing at -18°C for 2 hours, warming to room temperature, repeating the freezing step for 3 times, placing the solution in an oven at 80°C, reacting for 6 hours, taking out the mold, washing it with deionized water for 6 times, adding anhydrous ethanol 2 to 3 times the mass of the graphene solution, standing it until the anhydrous copper sulfate test does not change color, and drying it at 50°C for 24 hours to obtain the aerogel microcolumn.

[0022] Furthermore, in step (8), the catalyst is a mixture of one or more of triethylenediamine, dibutyltin dilaurate, and triethylamine; the foaming agent is a mixture of one or more of HCFC-141, CFC-11, and HCFC-141b; and the foam stabilizer is L-6900L or B8418.

[0023] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0024] The invention utilizes aerogel hollow microspheres to be deposited on modified aerogel microcolumns to prepare self-made fillers, which are co-foamed with polyurethane resin to form foam plastics to achieve shock absorption, mildew resistance and antistatic effects.

[0025] Firstly, the present invention uses a columnar in-situ forming mold as a template to prepare a graphene aerogel microcolumn, which serves as an elastic support in a plastic matrix and can generate energy dissipation under the action of an external force, thereby achieving a shock-absorbing effect; then, the surface pores are used to adsorb a rare earth aluminate sol, and the rare earth aluminate is loaded inside the aerogel through calcination, so that the aerogel has a luminous effect; then, 3-aminopropyltrimethoxysilane is grafted on the surface of the graphene aerogel microcolumn by means of a silicon-oxygen bond, and its amino group reacts with the acyl chloride of (E)-3-(3-nitrophenyl)acryloyl chloride to generate an amide structure; then, the (E)-3-(3-nitrophenyl)acryloyl chloride Nitrobenzene is reduced to aminobenzene, and the aminobenzene on the surface of graphene aerogel microcolumns is repolymerized to form a polyaniline conductive network, which effectively dissipates static charge and makes the plastic antistatic. At the same time, the high molecular network polymer on the surface of aerogel microcolumns plays an isolating and protective role on rare earth aluminates, reduces the influence of the outside world on the luminescent material, and improves the compatibility with the resin matrix. Therefore, the aerogel microcolumns are arranged in a disordered state in the resin matrix and overlap with each other to form a three-dimensional network structure. In addition, the chemical network structure of the surface polymer restrains the movement of the substrate chain segments, changes the conformation and orientation of the chain segments near the network structure, strengthens the conformation distribution, and increases the shock absorption effect.

[0026] Secondly, the amino group of 5-(2-chloroethaneamido)-2-hydroxy-benzoic acid reacts with the chloride ion of propargyl chloroformate to generate a propargyl carbamate structure, which can effectively inhibit the growth of mold and prevent the plastic from mildewing and corruption; then the chloride ion of 5-(2-chloroethaneamido)-2-hydroxy-benzoic acid reacts with the diethylamino group of 1-(5-bromo-2-hydroxyphenyl)-3-(diethylamino)-2-propen-1-one to generate a quaternary ammonium structure, which works together with the propargyl carbamate structure and bromide ion to improve The anti-mildew effect of plastics; polystyrene hollow spheres are used as templates, and cross-linked with formaldehyde on the template to form aerogel hollow microspheres. Under ultraviolet light, the aerogel hollow microspheres and aerogel microcolumns are double-bonded and polymerized, thereby being deposited on the surface of the aerogel microcolumns. The quaternary ammonium ion groups in the aerogel hollow microspheres and polyaniline further construct conductive pathways to improve the antistatic effect of plastics; and the hollow microspheres form hydrogen bonds with the resin matrix, and a pore structure is formed inside the matrix, which has a hysteresis effect on the movement recovery of the polyurethane macromolecular chains, thereby increasing the shock absorption effect. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the test methods of various indicators of the oxygen-insulated luminous plastics prepared in the following examples are as follows:

[0029] Shock absorption: The loss factor of the embodiment and the comparative example of the same size was measured according to GB / T 18258.

[0030] Antistatic property: the volume resistivity of the embodiment and the comparative example of the same size was tested according to GB / T 15662.

[0031] Antifungal property: The same size of the embodiment and the comparative example were uniaxially stretched, shaped, and cut to obtain a sample of 40×40×4 mm. The mold growth was tested according to GB / T 24128. The test strains were Aspergillus niger ATCC 6275, Penicillium variotii CBS628.66, Penicillium funiculum ATCC 9644, Trichoderma longibrachiatum ATCC 13631, and Mucor globosum ATCC 6205. The above strains were used to culture and prepare a 6.0×10 6 The five kinds of fungal spore suspensions are mixed to prepare a mixed bacterial solution before use.

[0032] Example 1

[0033] (1) 5-(2-chloroethaneamido)-2-hydroxy-benzoic acid and pyridine were mixed in a mass ratio of 1:7, cooled to 0°C, and propargyl chloroformate (0.1 times the mass of pyridine) was added, reacted at 0°C for 2 hours, and ice water was added until solids precipitated, and filtered to obtain propargyl carbamate compound;

[0034] (2) The propargyl carbamate compound, potassium iodide, tetrahydrofuran, and 1-(5-bromo-2-hydroxyphenyl)-3-(diethylamino)-2-propene-1-one were mixed in a mass ratio of 1:0.1:18:2, reacted at 80 rpm and 82°C for 46 hours, filtered, and the filter cake was washed twice with methanol and distilled water in sequence, and dried at 50°C and vacuum degree of -0.08 MPa for 24 hours to obtain an anti-mildew monomer compound;

[0035] (3) The polystyrene hollow spheres and the mildew-proof monomer compound solution were mixed in a mass ratio of 1:2, and the mass ratio of the mildew-proof monomer compound, formaldehyde, sodium hydroxide, and ethanol in the mildew-proof monomer compound solution was 1:0.5:0.007:2.7. After being placed at 25°C for 40 hours, an equal volume of dibutyl phthalate was added to the mildew-proof monomer compound solution, the temperature was raised to 35°C, and the mixture was stirred at 100 rpm for 24 hours. The mixture was filtered, and the solid was taken out and immersed in acetone 3 times the mass of the solid. The wet gel microspheres were obtained by soaking the mixture for 48 hours. The wet gel microspheres were placed in an autoclave, the temperature was lowered to 4°C, and liquid carbon dioxide was filled in to twice the height of the wet gel microspheres. The mixture was kept at 31°C and 7.3 MPa for 30 minutes, the pressure was increased to 8 MPa, the temperature was increased to 45°C, the pressure was reduced to normal pressure, and the hollow aerogel microspheres were obtained.

[0036] (4) Injecting graphene solution into a cylindrical in-situ molding mold with a diameter of 850 μm to 2 / 3 of the height of the cylindrical in-situ molding mold, the mass ratio of graphene oxide, deionized water, and vitamin C in the graphene solution is 0.4:100:0.8, placing it in an 80°C oven, reacting for 60 minutes, cooling it to room temperature, freezing it at -18°C for 2 hours, warming it to room temperature, repeating the above freezing steps 3 times, placing it in an 80°C oven, reacting for 6 hours, taking out the mold, washing it with deionized water 6 times, adding anhydrous ethanol twice the mass of the graphene solution, standing it until the anhydrous copper sulfate test does not change color, and drying it at 50°C for 24 hours to obtain an aerogel microcolumn;

[0037] (5) The aerogel microcolumn was placed in a luminescent powder precursor solution with a mass ratio of 0.5 times that of the aerogel microcolumn. The mass ratio of strontium chloride, europium nitrate, crystalline aluminum chloride, deionized water, and citric acid in the luminescent powder precursor solution was 1.02:0.07:1.97:40:2.52. After ultrasonic treatment at 90°C and 500W for 1 hour, the solution was taken out and placed in an oven at 110°C. After drying for 10 hours, the solution was placed in a tubular heat treatment furnace and heated to 700°C at a rate of 10°C / min. After being kept warm for 2 hours, the solution was cooled to room temperature. In a reducing atmosphere, the solution was heated to 900°C at the same rate and sintered for 4 hours. The volume ratio of nitrogen and hydrogen in the reducing atmosphere was 95:5. The solution was cooled to room temperature to obtain a luminescent aerogel microcolumn.

[0038] (6) The luminous aerogel microcolumns and deionized water were mixed at a mass ratio of 5:1200, and after stirring evenly, 3-aminopropyltrimethoxysilane solution with a mass of 6 times the mass of the luminous aerogel microcolumns was added, and the mass ratio of 3-aminopropyltrimethoxysilane solution to anhydrous ethanol in the 3-aminopropyltrimethoxysilane solution was 1:19. After ultrasonic treatment at 400W for 30 minutes, stirring at 100rpm for 10 minutes, hydrochloric acid was added until the solution pH was 4, and the reaction was carried out in a water bath at 50℃ for 2 hours, and then the temperature was raised to 70℃. After continuing the reaction for 2 hours, the solution was centrifuged at 18000rpm for 3 minutes, and the pretreated aerogel microcolumns were obtained by filtration;

[0039] (7) The pretreated aerogel microcolumn, tetrahydrofuran, and N,N-dimethylformamide were mixed in a mass ratio of 1:6:5.1. At 0°C, a solution of (E)-3-(3-nitrophenyl)acryloyl chloride with a mass of 4 times that of the pretreated aerogel microcolumn was added dropwise. The mass ratio of (E)-3-(3-nitrophenyl)acryloyl chloride to tetrahydrofuran in the solution was 1:3.5. After stirring at 60 rpm for 48 h, 80 times the mass of distilled water of the pretreated aerogel microcolumn was added. After stirring at 100 rpm for 20 min, the mixture was filtered, washed with deionized water for 4 times, and dried at 40°C and vacuum degree of -0.07 MPa for 12 h to obtain an amidated aerogel microcolumn.

[0040] (8) Tetrahydrofuran, amidated aerogel microcolumn, deionized water, iron powder, and 7.5% hydrochloric acid were mixed in a mass ratio of 10:1:3:1.6:0.5. After reacting for 7 hours, ethyl acetate 4 times the mass of the amidated aerogel microcolumn and sodium hydroxide 0.06 times the mass of the amidated aerogel microcolumn were added. After reacting at 50°C for 30 minutes, the mixture was filtered and washed with ethyl acetate and saturated sodium chloride for 5 times to obtain intermediate A. Hydrochloric acid with a mass fraction of 4.4%, intermediate A, and aniline were mixed in a mass ratio of 20:1:1. After stirring, an ammonium persulfate solution with a mass fraction of 19 times that of the intermediate A was added. The mass ratio of ammonium persulfate to 4.4% hydrochloric acid in the ammonium persulfate solution was 1:15. After reacting for 23 hours, the mixture was filtered and washed with 4.4% hydrochloric acid, ethanol, and distilled water for 6 times. The mixture was dried at 50°C and a vacuum degree of -0.09 MPa for 24 hours to obtain a modified aerogel microcolumn.

[0041] (9) Polyvinyl pyrrolidone, methanol, modified aerogel microcolumns, aerogel hollow microspheres, and azobisisobutyronitrile were mixed in a mass ratio of 3.5:68:8.4:4.1:1.2, and ultrasonicated at 400 W for 15 min, and then evacuated to 0.1 Pa with an intensity of 0.7 mW / cm 2 , after irradiating with ultraviolet light of wavelength 254nm for 24h, centrifuging at 15000rpm for 5min, filtering, washing with deionized water and anhydrous ethanol for 4 times in sequence, and drying at 0℃ and vacuum degree of -0.09MPa for 24h to obtain the homemade filler;

[0042] (10) A polyester polyol with a relative molecular weight of 3000, a flame retardant, a homemade filler, a foam stabilizer L-6900L, HCFC-141, and triethylenediamine were mixed in a mass ratio of 100:10:10:0.1:1:0.01. The mass ratio of diethyl phosphate, dimethyl methylphosphonate, and phenyl aluminum phosphite in the flame retardant was 1:1:1. After stirring evenly, 0.4 times the mass of hexamethylene diisocyanate was added to the polyester polyol. After reacting at 30°C and 100 rpm for 2 h, the mixture was injected into a mold at 50°C. After standing for 10 min, the mixture was placed in an oven at 70°C, aged for 1 h, cooled, and demolded to obtain an oxygen-insulated luminous plastic.

[0043] Example 2

[0044] (1) 5-(2-chloroethaneamido)-2-hydroxy-benzoic acid and pyridine were mixed in a mass ratio of 1:7, cooled to 0°C, and propargyl chloroformate (0.15 times the mass of pyridine) was added, reacted at 2°C for 2h, and ice water was added until solids precipitated, and filtered to obtain propargyl carbamate compound;

[0045] (2) The propargyl carbamate compound, potassium iodide, tetrahydrofuran, and 1-(5-bromo-2-hydroxyphenyl)-3-(diethylamino)-2-propene-1-one were mixed in a mass ratio of 1:0.15:18:2.5, reacted at 80 rpm and 82°C for 48 hours, filtered, and the filter cake was washed twice with methanol and distilled water in sequence, and dried at 50°C and vacuum degree of -0.08 MPa for 24 hours to obtain an anti-mildew monomer compound;

[0046] (3) The polystyrene hollow spheres and the mildew-proof monomer compound solution were mixed in a mass ratio of 1:3, and the mass ratio of the mildew-proof monomer compound, formaldehyde, sodium hydroxide, and ethanol in the mildew-proof monomer compound solution was 1:0.65:0.007:3.1. After being placed at 25°C for 44 hours, an equal volume of dibutyl phthalate was added to the mildew-proof monomer compound solution, the temperature was raised to 35°C, and the mixture was stirred at 110 rpm for 24 hours. The mixture was filtered, and the solid was taken out and immersed in acetone 3.5 times the mass of the solid. The wet gel microspheres were obtained by soaking the mixture for 48 hours. The wet gel microspheres were placed in an autoclave, the temperature was lowered to 5°C, and liquid carbon dioxide was filled in to 3 times the height of the wet gel microspheres. The mixture was kept at 31°C and 7.3 MPa for 35 minutes, the pressure was increased to 9 MPa, the temperature was increased to 47°C, and the pressure was reduced to normal pressure to obtain aerogel hollow microspheres.

[0047] (4) Injecting graphene solution into a cylindrical in-situ molding mold with a diameter of 850 μm to 2 / 3 of the height of the cylindrical in-situ molding mold, the mass ratio of graphene oxide, deionized water, and vitamin C in the graphene solution is 0.4:100:0.8, placing it in an 80°C oven, reacting for 60 minutes, cooling it to room temperature, freezing it at -18°C for 2 hours, and then warming it to room temperature. Repeat the above freezing steps 3 times, placing it in an 80°C oven, reacting for 6 hours, taking out the mold, washing it with deionized water 6 times, adding anhydrous ethanol 2.5 times the mass of the graphene solution, standing it until the anhydrous copper sulfate test does not change color, and drying it at 50°C for 24 hours to obtain an aerogel microcolumn;

[0048] (5) The aerogel microcolumn was placed in a luminescent powder precursor solution with a mass ratio of 0.85 times that of the aerogel microcolumn. The mass ratio of strontium chloride, europium nitrate, crystalline aluminum chloride, deionized water, and citric acid in the luminescent powder precursor solution was 1.02:0.07:1.97:40:2.52. After ultrasonic treatment at 90°C and 500W for 1.5 hours, the solution was taken out and placed in a 110°C oven. After drying for 15 hours, the solution was placed in a tubular heat treatment furnace and heated to 700°C at a rate of 10°C / min. After keeping the temperature for 2.5 hours, the solution was cooled to room temperature. Under a reducing atmosphere, the solution was heated to 1050°C at the same rate and sintered for 4 hours. The volume ratio of nitrogen and hydrogen in the reducing atmosphere was 95:5. The solution was cooled to room temperature to obtain a luminescent aerogel microcolumn.

[0049] (6) Mix the luminous aerogel microcolumns and deionized water in a mass ratio of 5:1200, stir evenly, add 3-aminopropyltrimethoxysilane solution with a mass of 9.5 times the mass of the luminous aerogel microcolumns, and the mass ratio of 3-aminopropyltrimethoxysilane solution to anhydrous ethanol in the 3-aminopropyltrimethoxysilane solution is 1:25.5. After ultrasonic treatment at 450W for 30min, stir at 110rpm for 10min, add hydrochloric acid until the solution pH is 4.5, react in a water bath at 50℃ for 2.5h, heat to 70℃, continue to react for 2.5h, centrifuge at 18000rpm for 4min, and filter to obtain the pretreated aerogel microcolumns;

[0050] (7) The pretreated aerogel microcolumn, tetrahydrofuran, and N,N-dimethylformamide were mixed in a mass ratio of 1:6:5.1. At 0°C, 4.5 times the mass of the pretreated aerogel microcolumn (E)-3-(3-nitrophenyl) acryloyl chloride solution was added dropwise. The mass ratio of (E)-3-(3-nitrophenyl) acryloyl chloride to tetrahydrofuran in the (E)-3-(3-nitrophenyl) acryloyl chloride solution was 1:3.5. After stirring at 70 rpm for 48 h, 82.5 times the mass of the pretreated aerogel microcolumn was added with distilled water. After stirring at 150 rpm for 25 min, the mixture was filtered, washed with deionized water for 4 times, and dried at 40°C and vacuum degree of -0.07 MPa for 12 h to obtain the amidated aerogel microcolumn.

[0051] (8) Tetrahydrofuran, amidated aerogel microcolumns, deionized water, iron powder, and 7.5% hydrochloric acid were mixed in a mass ratio of 11:1:3.5:1.75:0.55, and reacted for 7.5 h. Then, ethyl acetate (4 times the mass of the amidated aerogel microcolumns) and sodium hydroxide (0.06 times the mass of the amidated aerogel microcolumns) were added. After reacting at 50 °C for 35 min, the mixture was filtered and washed with ethyl acetate and saturated sodium chloride for 5 times to obtain intermediate A. The mass fraction of 4.4 % hydrochloric acid, intermediate A, and aniline were mixed in a mass ratio of 25:1:1.25, and after stirring evenly, an ammonium persulfate solution with a mass ratio of 19.5 times that of the intermediate A was added, and the mass ratio of ammonium persulfate to 4.4% hydrochloric acid in the ammonium persulfate solution was 1:15. After reacting for 24 hours, the mixture was filtered, and washed with 4.4% hydrochloric acid, ethanol, and distilled water for 6 times in sequence, and dried at 50°C and a vacuum degree of -0.09MPa for 24 hours to obtain a modified aerogel microcolumn;

[0052] (9) Polyvinyl pyrrolidone, methanol, modified aerogel microcolumns, aerogel hollow microspheres, and azobisisobutyronitrile were mixed in a mass ratio of 4.6:75.5:12.7:6:1.2, and ultrasonicated at 450 W for 15 min. The mixture was then evacuated to 0.3 Pa with an intensity of 0.7 mW / cm 2, after irradiating with ultraviolet light at a wavelength of 254 nm for 25 hours, centrifuging at 15000 rpm for 7 minutes, filtering, washing with deionized water and anhydrous ethanol for 4 times in sequence, and drying at 0°C and a vacuum degree of -0.09 MPa for 24 hours to obtain the homemade filler;

[0053] (10) A polyether polyol with a relative molecular weight of 4200, a flame retardant, a homemade filler, B841, CFC-11, and dibutyltin dilaurate were mixed in a mass ratio of 125:15:20:2.5:2.5:1. The mass ratio of diethyl phosphate, dimethyl methylphosphonate, and aluminum phenylphosphite in the flame retardant was 1:1.15:1.25. After stirring evenly, 0.45 times the mass of hexamethylene diisocyanate of the polyether polyol was added. After reacting at 35°C and 150 rpm for 2.5 hours, the mixture was injected into a mold at 55°C. After standing for 15 minutes, the mixture was placed in an oven at 80°C, aged for 1.5 hours, cooled, and demolded to obtain an oxygen-insulated luminous plastic.

[0054] Example 3

[0055] (1) 5-(2-chloroethaneamido)-2-hydroxy-benzoic acid and pyridine were mixed in a mass ratio of 1:7, cooled to 0°C, and propargyl chloroformate (0.2 times the mass of pyridine) was added, reacted at 4°C for 2h, and ice water was added until solids precipitated, and filtered to obtain propargyl carbamate compound;

[0056] (2) The propargyl carbamate compound, potassium iodide, tetrahydrofuran, and 1-(5-bromo-2-hydroxyphenyl)-3-(diethylamino)-2-propene-1-one were mixed in a mass ratio of 1:0.2:18:3, reacted at 80 rpm and 82°C for 50 hours, filtered, and the filter cake was washed twice with methanol and distilled water in sequence, and dried at 50°C and vacuum degree of -0.08 MPa for 24 hours to obtain a mildew-proof monomer compound;

[0057] (3) The polystyrene hollow spheres and the mildew-proof monomer compound solution are mixed in a mass ratio of 1:4, and the mass ratio of the mildew-proof monomer compound, formaldehyde, sodium hydroxide, and ethanol in the mildew-proof monomer compound solution is 1:0.8:0.007:3.5. After being placed at 25°C for 48 hours, an equal volume of dibutyl phthalate is added to the mildew-proof monomer compound solution, the temperature is raised to 35°C, and the mixture is stirred at 120 rpm for 24 hours. The mixture is filtered, and the solid is taken out and immersed in acetone 4 times the mass of the solid. The wet gel microspheres are obtained by soaking the mixture for 48 hours. The wet gel microspheres are placed in an autoclave, the temperature is lowered to 6°C, and liquid carbon dioxide is filled in to 4 times the height of the wet gel microspheres. The mixture is maintained at 31°C and 7.3 MPa for 40 minutes, the pressure is increased to 10 MPa, the temperature is increased to 50°C, and the mixture is maintained for 4 hours. The pressure is then released to normal pressure to obtain the aerogel hollow microspheres.

[0058] (4) Injecting graphene solution into a cylindrical in-situ molding mold with a diameter of 850 μm to 2 / 3 of the height of the cylindrical in-situ molding mold, the mass ratio of graphene oxide, deionized water, and vitamin C in the graphene solution is 0.4:100:0.8, placing it in an 80°C oven, reacting for 60 minutes, cooling to room temperature, freezing at -18°C for 2 hours, and then warming to room temperature. Repeat the above freezing steps 3 times, placing it in an 80°C oven, reacting for 6 hours, taking out the mold, washing it with deionized water 6 times, adding anhydrous ethanol 3 times the mass of the graphene solution, standing until the anhydrous copper sulfate test does not change color, and drying at 50°C for 24 hours to obtain an aerogel microcolumn;

[0059] (5) The aerogel microcolumn was placed in a luminescent powder precursor solution with a mass ratio of 1.2 times that of the aerogel microcolumn. The mass ratio of strontium chloride, europium nitrate, crystalline aluminum chloride, deionized water, and citric acid in the luminescent powder precursor solution was 1.02:0.07:1.97:40:2.52. After ultrasonic treatment at 90°C and 500W for 2 hours, the solution was taken out and placed in an oven at 110°C. After drying for 20 hours, the solution was placed in a tubular heat treatment furnace and heated to 700°C at a rate of 10°C / min. After being kept warm for 3 hours, the solution was cooled to room temperature. In a reducing atmosphere, the solution was heated to 1200°C at the same rate and sintered for 4 hours. The volume ratio of nitrogen and hydrogen in the reducing atmosphere was 95:5. The solution was cooled to room temperature to obtain a luminescent aerogel microcolumn.

[0060] (6) The luminous aerogel microcolumns and deionized water were mixed at a mass ratio of 5:1200, and after stirring evenly, 3-aminopropyltrimethoxysilane solution with a mass of 13 times the mass of the luminous aerogel microcolumns was added, and the mass ratio of 3-aminopropyltrimethoxysilane solution to anhydrous ethanol in the 3-aminopropyltrimethoxysilane solution was 1:32. After 500W ultrasound for 30 minutes, stirring at 120rpm for 10 minutes, hydrochloric acid was added until the solution pH was 5, and the reaction was carried out in a water bath at 50℃ for 3 hours, and then the temperature was raised to 70℃. After continuing the reaction for 3 hours, the solution was centrifuged at 18000rpm for 5 minutes, and the pretreated aerogel microcolumns were obtained by filtration;

[0061] (7) The pretreated aerogel microcolumn, tetrahydrofuran, and N,N-dimethylformamide were mixed in a mass ratio of 1:6:5.1. At 0°C, a solution of (E)-3-(3-nitrophenyl)acryloyl chloride with a mass of 5 times that of the pretreated aerogel microcolumn was added dropwise. The mass ratio of (E)-3-(3-nitrophenyl)acryloyl chloride to tetrahydrofuran in the solution was 1:3.5. After stirring at 80 rpm for 48 h, 85 times the mass of distilled water of the pretreated aerogel microcolumn was added. After stirring at 200 rpm for 30 min, the mixture was filtered, washed with deionized water for 4 times, and dried at 40°C and vacuum degree of -0.07 MPa for 12 h to obtain an amidated aerogel microcolumn.

[0062] (8) Tetrahydrofuran, amidated aerogel microcolumn, deionized water, iron powder, and 7.5% hydrochloric acid were mixed in a mass ratio of 12:1:4:1.9:0.6. After reacting for 8 hours, ethyl acetate 4 times the mass of the amidated aerogel microcolumn and sodium hydroxide 0.06 times the mass of the amidated aerogel microcolumn were added. After reacting at 50°C for 40 minutes, the mixture was filtered and washed with ethyl acetate and saturated sodium chloride for 5 times to obtain intermediate A. Hydrochloric acid with a mass fraction of 4.4%, intermediate A, and aniline were mixed in a mass ratio of 30:1:1.5. After stirring evenly, an ammonium persulfate solution with a mass ratio of 20 times the mass of intermediate A was added. The mass ratio of ammonium persulfate to 4.4% hydrochloric acid in the ammonium persulfate solution was 1:15. After reacting for 25 hours, the mixture was filtered and washed with 4.4% hydrochloric acid, ethanol, and distilled water for 6 times. The mixture was dried at 50°C and a vacuum degree of -0.09 MPa for 24 hours to obtain a modified aerogel microcolumn.

[0063] (9) Polyvinyl pyrrolidone, methanol, modified aerogel microcolumns, aerogel hollow microspheres, and azobisisobutyronitrile were mixed in a mass ratio of 5.7:83:17:8:1.2, and ultrasonicated at 500 W for 15 min. The mixture was then evacuated to 0.5 Pa with an intensity of 0.7 mW / cm 2 , after irradiation with ultraviolet light of wavelength 254nm for 26h, centrifugation at 15000rpm for 8min, filtration, washing with deionized water and anhydrous ethanol for 4 times in sequence, and drying at 0℃ and vacuum degree of -0.09MPa for 24h to obtain the homemade filler;

[0064] (10) Sorbitol, flame retardant, homemade filler, B841, HCFC-141b, and triethylamine were mixed in a mass ratio of 150:20:30:5:5:2. The mass ratio of diethyl phosphate, dimethyl methylphosphonate, and aluminum phenylphosphite in the flame retardant was 1:1.3:1.5. After stirring evenly, 0.5 times the mass of diphenylmethane diisocyanate was added. After reacting at 40°C and 200 rpm for 3 h, the mixture was injected into a mold at 60°C. After standing for 20 min, the mixture was placed in an oven at 90°C, aged for 2 h, cooled, and demolded to obtain an oxygen-insulated luminous plastic.

[0065] Comparative Example 1

[0066] The difference between Comparative Example 1 and Example 2 is that step (1) is omitted, and step (2) is changed to: 5-(2-chloroethaneamido)-2-hydroxy-benzoic acid, potassium iodide, tetrahydrofuran, and 1-(5-bromo-2-hydroxyphenyl)-3-(diethylamino)-2-propene-1-one are mixed in a mass ratio of 1:0.15:18:2.5, reacted at 80 rpm and 82° C. for 48 h, filtered, and the filter cake is washed twice with methanol and distilled water in sequence, and dried at 50° C. and vacuum degree of -0.08 MPa for 24 h to obtain a mildew-proof monomer compound. The remaining steps are the same as those of Example 2.

[0067] Comparative Example 2

[0068] The difference between Comparative Example 2 and Example 2 is that there is no step (2), and step (1) is changed to: 5-(2-chloroethaneamido)-2-hydroxy-benzoic acid and pyridine are mixed in a mass ratio of 1:7, cooled to 0°C, propargyl chloroformate in an amount of 0.15 times the mass of pyridine is added, reacted at 2°C for 2h, ice water is added until solids precipitate, and filtered to obtain the anti-mildew monomer compound. The remaining steps are the same as those in Example 2.

[0069] Comparative Example 3

[0070] The difference between Comparative Example 3 and Example 2 is that there is no step (9), and step (10) is changed to: polyether polyol with a relative molecular weight of 4200, flame retardant, hollow aerogel microparticles, modified aerogel microcolumns, B841, CFC-11, and dibutyltin dilaurate are mixed in a mass ratio of 125:15:10:10:2.5:2.5:1, and the mass ratio of diethyl phosphate, dimethyl methylphosphonate, and aluminum phenylphosphinate in the flame retardant is 1:1.15:1.25. After stirring evenly, hexamethylene diisocyanate with a mass of 0.45 times that of the polyether polyol is added, and the reaction is carried out at 35°C and 150 rpm for 2.5 hours, and then injected into a mold at 55°C, and after standing for 15 minutes, it is placed in an oven at 80°C, aged for 1.5 hours, cooled and demolded to obtain an oxygen-insulated luminous plastic. The remaining steps are the same as those in Example 2.

[0071] Comparative Example 4

[0072] The difference between Comparative Example 4 and Example 2 is that there is no step (4), and step (5) is changed to: placing graphene oxide in a luminescent powder precursor solution with a mass ratio of 0.85 times that of graphene oxide, wherein the mass ratio of strontium chloride, europium nitrate, crystalline aluminum chloride, deionized water, and citric acid in the luminescent powder precursor solution is 1.02:0.07:1.97:40:2.52, and after ultrasonic treatment at 90°C and 500W for 1.5 hours, the solution is taken out and placed in an oven at 110°C, dried for 15 hours, and then placed in a tubular heat treatment furnace, heated to 700°C at 10°C / min, kept warm for 2.5 hours, cooled to room temperature, heated to 1050°C at the same speed under a reducing atmosphere, sintered for 4 hours, and the volume ratio of nitrogen and hydrogen in the reducing atmosphere is 95:5, and cooled to room temperature to obtain a luminescent aerogel microcolumn. The remaining steps are the same as those in Example 2.

[0073] Comparative Example 5

[0074] The difference between Comparative Example 5 and Example 2 is that there are no steps (6) to (8), and step (9) is changed to: polyvinyl pyrrolidone, methanol, luminous aerogel microcolumns, aerogel hollow microspheres, and azobisisobutyronitrile are mixed in a mass ratio of 4.6:75.5:12.7:6:1.2, and after ultrasonic treatment at 450W for 15min, the mixture is evacuated to 0.3Pa with an intensity of 0.7mW / cm2 , irradiated with ultraviolet light of wavelength 254nm for 25h, centrifuged at 15000rpm for 7min, filtered, washed with deionized water and anhydrous ethanol 4 times in sequence, and dried at 0℃ and vacuum degree of -0.09MPa for 24h to obtain the self-made filler. The remaining steps are the same as those in Example 2.

[0075] Effect example

[0076] Table 1 below shows the performance analysis results of the oxygen-isolating luminous plastics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0077] Table 1

[0078]

[0079] It can be seen from the loss factor experimental data of the embodiments and comparative examples that the present invention uses aerogel microcolumns as elastic supports in the plastic matrix, which can generate energy dissipation, thereby achieving a shock-absorbing effect. In addition, the chemical network structure of the aerogel hollow microspheres and the surface polymer constrains the movement of the substrate segments, changes the conformation and orientation of the segments near the network structure, strengthens the conformation distribution, and increases the shock-absorbing effect. It can be seen from the mold growth experimental data of the embodiments and comparative examples that the present invention uses 5-(2-chloroethaneamido)-2-hydroxy-benzoic acid, propargyl chloroformate, and 1-(5-bromo-2-hydroxyphenyl)-3-(diethylamino)-2-propene-1-one to generate a mildew-proof monomer compound. The propargyl carbamate structure, quaternary ammonium and bromide ions work together to effectively inhibit mold growth and prevent plastic from mildew and corruption. It can be seen from the volume resistance experimental data of the embodiments and the comparative examples that the present invention uses 3-aminopropyltrimethoxysilane and (E)-3-(3-nitrophenyl) acryloyl chloride to modify the graphene aerogel microcolumns to form a polyaniline conductive network on the surface, which effectively dissipates static charge, makes the plastic have an antistatic effect, and improves the compatibility with the resin matrix. Therefore, the disordered arrangement and overlapping form a three-dimensional network structure, which increases the antistatic property. At the same time, the quaternary ammonium ion groups in the aerogel hollow microspheres and the polyaniline further construct a conductive path to improve the antistatic effect of the plastic.

[0080] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing oxygen-insulated luminous plastic, characterized in that: The method comprises the following preparation steps: (1) 5-(2-chloroethaneamido)-2-hydroxy-benzoic acid and pyridine were mixed in a mass ratio of 1:7, cooled to 0°C, and propargyl chloroformate (0.15 times the mass of pyridine) was added, reacted at 2°C for 2h, and ice water was added until solids precipitated, and filtered to obtain propargyl carbamate compound; (2) The propargyl carbamate compound, potassium iodide, tetrahydrofuran, and 1-(5-bromo-2-hydroxyphenyl)-3-(diethylamino)-2-propene-1-one were mixed in a mass ratio of 1:0.15:18:2.5, reacted at 80 rpm and 82°C for 48 hours, filtered, and the filter cake was washed twice with methanol and distilled water in sequence, and dried at 50°C and vacuum degree of -0.08 MPa for 24 hours to obtain an anti-mildew monomer compound; (3) The polystyrene hollow spheres and the mildew-proof monomer compound solution were mixed in a mass ratio of 1:3, and the mass ratio of the mildew-proof monomer compound, formaldehyde, sodium hydroxide, and ethanol in the mildew-proof monomer compound solution was 1:0.65:0.007:3.

1. After being placed at 25°C for 44 hours, an equal volume of dibutyl phthalate was added to the mildew-proof monomer compound solution, the temperature was raised to 35°C, and the mixture was stirred at 110 rpm for 24 hours. The mixture was filtered, and the solid was taken out and immersed in acetone 3.5 times the mass of the solid. The wet gel microspheres were obtained by soaking the mixture for 48 hours. The wet gel microspheres were placed in an autoclave, the temperature was lowered to 5°C, and liquid carbon dioxide was filled in to 3 times the height of the wet gel microspheres. The mixture was kept at 31°C and 7.3 MPa for 35 minutes, the pressure was increased to 9 MPa, the temperature was increased to 47°C, and the pressure was reduced to normal pressure to obtain aerogel hollow microspheres. (4) Injecting graphene solution into a cylindrical in-situ molding mold with a diameter of 850 μm to 2 / 3 of the height of the cylindrical in-situ molding mold, the mass ratio of graphene oxide, deionized water, and vitamin C in the graphene solution is 0.4:100:0.8, placing it in an 80°C oven, reacting for 60 minutes, cooling it to room temperature, freezing it at -18°C for 2 hours, and then warming it to room temperature. Repeat the above freezing steps 3 times, placing it in an 80°C oven, reacting for 6 hours, taking out the mold, washing it with deionized water 6 times, adding anhydrous ethanol 2.5 times the mass of the graphene solution, standing it until the anhydrous copper sulfate test does not change color, and drying it at 50°C for 24 hours to obtain an aerogel microcolumn; (5) The aerogel microcolumn was placed in a luminescent powder precursor solution with a mass ratio of 0.85 times that of the aerogel microcolumn. The mass ratio of strontium chloride, europium nitrate, crystalline aluminum chloride, deionized water, and citric acid in the luminescent powder precursor solution was 1.02:0.07:1.97:40:2.

52. After ultrasonic treatment at 90°C and 500W for 1.5 hours, the solution was taken out and placed in a 110°C oven. After drying for 15 hours, the solution was placed in a tubular heat treatment furnace and heated to 700°C at a rate of 10°C / min. After keeping the temperature for 2.5 hours, the solution was cooled to room temperature. Under a reducing atmosphere, the solution was heated to 1050°C at the same rate and sintered for 4 hours. The volume ratio of nitrogen and hydrogen in the reducing atmosphere was 95:

5. The solution was cooled to room temperature to obtain a luminescent aerogel microcolumn. (6) Mix the luminous aerogel microcolumns and deionized water in a mass ratio of 5:1200, stir evenly, add 3-aminopropyltrimethoxysilane solution with a mass of 9.5 times the mass of the luminous aerogel microcolumns, and the mass ratio of 3-aminopropyltrimethoxysilane solution to anhydrous ethanol in the 3-aminopropyltrimethoxysilane solution is 1:25.

5. After ultrasonic treatment at 450W for 30min, stir at 110rpm for 10min, add hydrochloric acid until the solution pH is 4.5, react in a water bath at 50℃ for 2.5h, heat to 70℃, continue to react for 2.5h, centrifuge at 18000rpm for 4min, and filter to obtain the pretreated aerogel microcolumns; (7) The pretreated aerogel microcolumn, tetrahydrofuran, and N,N-dimethylformamide were mixed in a mass ratio of 1:6:5.

1. At 0°C, 4.5 times the mass of the pretreated aerogel microcolumn (E)-3-(3-nitrophenyl) acryloyl chloride solution was added dropwise. The mass ratio of (E)-3-(3-nitrophenyl) acryloyl chloride to tetrahydrofuran in the (E)-3-(3-nitrophenyl) acryloyl chloride solution was 1:3.

5. After stirring at 70 rpm for 48 h, 82.5 times the mass of the pretreated aerogel microcolumn was added with distilled water. After stirring at 150 rpm for 25 min, the mixture was filtered, washed with deionized water for 4 times, and dried at 40°C and vacuum degree of -0.07 MPa for 12 h to obtain the amidated aerogel microcolumn. (8) Tetrahydrofuran, amidated aerogel microcolumns, deionized water, iron powder, and 7.5% hydrochloric acid were mixed in a mass ratio of 11:1:3.5:1.75:0.55, and reacted for 7.5 h. Then, ethyl acetate (4 times the mass of the amidated aerogel microcolumns) and sodium hydroxide (0.06 times the mass of the amidated aerogel microcolumns) were added. After reacting at 50 °C for 35 min, the mixture was filtered and washed with ethyl acetate and saturated sodium chloride for 5 times to obtain intermediate A. The mixture with a mass fraction of 4. 4% hydrochloric acid, intermediate A, and aniline were mixed in a mass ratio of 25:1:1.25, and after being stirred evenly, an ammonium persulfate solution with a mass fraction of 19.5 times that of the intermediate A was added, and the mass ratio of ammonium persulfate to 4.4% hydrochloric acid in the ammonium persulfate solution was 1:

15. After reacting for 24 hours, the mixture was filtered, and washed with 4.4% hydrochloric acid, ethanol, and distilled water for 6 times in sequence, and dried at 50°C and a vacuum degree of -0.09 MPa for 24 hours to obtain a modified aerogel microcolumn. (9) Polyvinyl pyrrolidone, methanol, modified aerogel microcolumns, aerogel hollow microspheres, and azobisisobutyronitrile were mixed in a mass ratio of 4.6:75.5:12.7:6:1.2, and subjected to ultrasonic treatment at 450 W for 15 min. The mixture was evacuated to 0.3 Pa, irradiated with ultraviolet light at an intensity of 0.7 mW / cm2 and a wavelength of 254 nm for 25 h, centrifuged at 15,000 rpm for 7 min, filtered, washed four times with deionized water and anhydrous ethanol, and dried at 0°C and a vacuum degree of -0.09 MPa for 24 h to obtain a self-made filler. (10) A polyether polyol with a relative molecular weight of 4200, a flame retardant, a homemade filler, B8418, CFC-11, and dibutyltin dilaurate were mixed in a mass ratio of 125:15:20:2.5:2.5:

1. The mass ratio of diethyl phosphate, dimethyl methylphosphonate, and aluminum phenylphosphite in the flame retardant was 1:1.15:1.

25. After stirring evenly, 0.45 times the mass of hexamethylene diisocyanate of the polyether polyol was added. After reacting at 35°C and 150 rpm for 2.5 hours, the mixture was injected into a mold at 55°C. After standing for 15 minutes, the mixture was placed in an oven at 80°C, aged for 1.5 hours, cooled, and demolded to obtain an oxygen-insulated luminous plastic.